Pengaruh Latihan Drill Passing dan Rondo Terhadap Akurasi Passing - Khanif, Mohammad Naufal; Puriana, Ramadhany Hananto; Wahyono, Muhammad (Jurnal Porkes, 2025)
This study aims to determine the level of passing accuracy using the drill passing and rondo method training techniques in extracurricular futsal students of smp negeri 6 sidoarjo. The research method used is quantitative with a two group pretest and posttest design. The population of this study were 12 people. Sample determination using purposive sampling. The instrument used in this study is a passing accuracy test, with an indicator of the ability to enter the ball into the goal with a distance of 10 meters. Experiment A results, > 8 as much as 1 (6.6%), 6-7 values as much as 6 (40%), 1-5 values as much as 8 (53.4%). Experimental posttest distribution values > 8 as many as 5 (33.3%%), 6-7 values as many as 4 (26.7%), 1-5 values as many as 6 (40%). group B, > 8 as many as 1 (6.6%), 6-7 values as many as 5 (33.3%), 1-5 values as many as 9 (60%), The experimental posttest distribution values > 8 were 2 (13.3%), 6-7 were 4 (26.7%), 1-5 were 9 (60%), sig. (2-tailed) in group A is .001, in group B is .056, so the sig. (2-tailed) in group A < 0.05, it can be stated that the use of the drill passing method has an effect on the success of improving passing accuracy in extracurricular futsal students. It is concluded that passing drill training has a greater influence on improving passing accuracy compared to rondo training.